MANUSIA, EKOLOGI DAN TEOLOGI: Kajian Eko-Teologi Terhadap Krisis Lingkungan di Pantai Galala - Brayen Patty (IAKN Ambon, 2021)
Contemporary theology also pays attention to the environment. Since ancient times, anthropocentrism has developed in the meaning of theology. Today's theology presents a universal concept of salvation in which the environment also obtains the salvation that is given through the salvation of Jesus. Various environmental-based theological concepts have emerged, such as green theology and so on. This concept is here to provide answers to the environmental crisis that occurred. In this paper, the concept of human position, ecology and theology will be studied. This article is a study that presents accusations against anthropocentrism and provides a middle way to answer the environmental crisis.